Gene expression profile of murine long-term reconstituting vs. short-term reconstituting hematopoietic stem cells - Zhong, Jiang F. (National Academy of Sciences, 2005)
The hematopoietic stem cell (HSC) compartment is composed of long-term reconstituting (LTR) and short-term reconstituting (STR) stem cells. LTR HSC can reconstitute the hematopoietic system for life, whereas STR HSC can sustain hematopoiesis for only a few weeks in the mouse. Several excellent gene expression profiles have been obtained of the total hematopoietic stem cell population. We have used five-color FACS sorting to isolate separate populations of LTR and STR stem cell subsets. The LTR HSC has the phenotype defined as Lin(-) Sca(+) Kit(+) 38(+) 34(-); two subsets of STR HSC were obtained with phenotypes of Lin(-) Sca(+) Kit(+) 38(+) 34(+) and Lin(-) Sca(+) Kit(+) 38(-) 34(+). The microarray profiling study reported here was able to identify genes specific for LTR functions. In the interrogated genes (≈12,000 probe sets corresponding to 8,000 genes), 210 genes are differentially expressed, and 72 genes are associated with LTR activity, including membrane proteins, signal transduction molecules, and transcription factors. Hierarchical clustering of the 210 differentially expressed genes suggested that they are not bone marrow-specific but rather appear to be stem cell-specific. Transcription factor-binding site analysis suggested that GATA3 might play an important role in the biology of LTR HSC.